Мethodological foundations of life competencies graduates of boarding schools (Pedagogy of Higher and Secondary Education, 2012)
Yakovlevа V. Мethodological foundations of life competencies graduates of boarding schools.In the article refers to the possibility of forming life competence graduates of boarding schools by means of special training. Special training is presented as a interaction technology.
Keywords: competence; life competence; interactive technology; specialized education; graduates of boarding schools